Las relaciones entre México y Cuba después del 11 de septiembre y el papel de EE.UU. - Pablo Telman Sánchez Ramírez (Revista Enfoques, 2008)
For several decades, Mexican-Cuban relations left apart ideological issues, what allowed the development of a constant and stable bi-lateral relationship: Mexican stance towards Cuba featured an explicit support towards the Cuban process, the former becoming thechief Latin American investor on the island, and the latter its second main business partner in the Caribbean. According to the author, the relationship between Mexico and Cuba has been modified, due to pressures from the US governement: the Mexican governmentis currently subordinated to Washington, a situation that has meant a rupture with Latin America as a whole and Cuba specifically. Finally, the author indicates that the conditions are favorable for a Mexican change of attitude towards the re-establishment of an assertive and independent foreign policy, which would lead to the recovery of its leadership and prestige in Latin America.